Rapid establishment of a flowering cline in Medicago polymorpha after invasion of North America. Issue 23 (10th December 2018) - Helliwell, Emily E.; Faber‐Hammond, Joshua; Lopez, Zoie C.; Garoutte, Aaron; von Wettberg, Eric; Friesen, Maren L.; Porter, Stephanie S.
Abstract: To establish and spread in a new location, an invasive species must be able to carry out its life cycle in novel environmental conditions. A key trait underlying fitness is the shift from vegetative to reproductive growth through floral development. In this study, we used a common garden experiment and genotyping‐by‐sequencing to test whether the latitudinal flowering cline of the North American invasive plant Medicago polymorpha was translocated from its European native range through multiple introductions, or whether the cline rapidly established due to evolution following a genetic bottleneck. Analysis of flowering time in 736 common garden plants showed a latitudinal flowering time cline in both the native and invaded ranges where genotypes from lower latitudes flowered earlier. Genotyping‐by‐sequencing of 9, 658 SNPs in 446 individuals revealed two major subpopulations of M. polymorpha in the native range, only one of which is present in the invaded range. Additionally, native range populations have higher genetic diversity than invaded range populations, suggesting that a genetic bottleneck occurred during invasion. All invaded range individuals are closely related to plants collected from native range populations in Portugal and southern Spain, and population assignment tests assigned invaded range individuals to this same narrow source region. Taken together, our results suggest that latitudinal clinal variation in flowering time has rapidly evolved across the invaded range despite a genetic bottleneck following introduction.